Neogene Epeirogeny of Iberia. (25th February 2019) - Conway‐Jones, Benedict W.; Roberts, Gareth G.; Fichtner, Andreas; Hoggard, Mark
Abstract: The origin of Iberia's topography is examined by combining gravity, magmatic, topographic, and seismological observations with geomorphic considerations. We have four principal results. First, the highest coherence between free‐air gravity and topography is at wavelengths ≲ 250 km where admittance indicates that elastic thickness of Iberia's plate is 20 ± 3 km. These results imply that flexural and subplate support of Iberian topography could be expressed at wavelengths of O(100) km. Second, P‐to‐S receiver functions and simple isostatic calculations indicate that while crustal thickness variations and flexural loading (e.g., as a result of plate shortening) partially explain the elevation of Pyrenean, Betics, Cantabrian, Spanish Central System, and Iberian Chain topography, they fail to explain the elevation of large parts of Iberia. Third, a new full waveform shear wave tomographic model and velocity to temperature conversions suggest that the asthenosphere beneath Iberia is anomalously slow and has excess temperatures of up to 162 ± 14 °C. Simple isostatic calculations indicate asthenospheric support of topography of up to 1 km. Neogene‐Recent (∼23–0 Ma) extrusive magmatism (e.g., Calatrava, Catalan) sit atop many of the slow shear wave velocity anomalies. Finally, biostratigraphic data, combined with inversion of 3, 217 river profiles, show that most of Iberia's topography grew during the last ∼30 Ma at rates of up to 0.3 mm/year. Best‐fitting theoretical rivers have a low residual root‐mean‐square misfit (=0.96) and calculated uplift is consistent with an independent inventory of stratigraphic and biostratigraphic observations. We suggest that Neogene‐Recent growth of most of central Iberia's topography was a result of asthenospheric support. Key Points: Calculated history of dynamic support of Iberia Excess asthenospheric temperatures support up to 1 km of topography Marine terraces and geomorphology suggest growth of support in last ∼30 Ma